Podium and Influence: A Network Analysis of the Most Important Formula One Drivers - Faria, José Geraldo Rigotti de; Ferreira, Fernando Guimarães (Anais do Brazilian Workshop on Social Network Analysis and Mining (BraSNAM), 2024)
This paper presents a network analysis to recognize the most important Formula One drivers, focusing on podium finishes as a metric of influence. We investigated a dataset comprising 855 drivers, 1,079 races, and 25,840 results to explore the relationships and performance dynamics among drivers. The use of centrality measures and community detection in network analysis offers a novel approach to evaluating Formula One drivers, beyond traditional metrics like championship or race wins. In our comprehensive analysis, it was determined that PageRank yielded the most insightful results, effectively capturing the essential contributions and setting a new benchmark for assessing excellence in Formula One racing and other sports.